Circulating tumor DNA detection in head and neck cancer: evaluation of two different detection approaches - Perdomo, Sandra; Avogbe, Patrice H; Foll, Matthieu; Abedi-Ardekani, Behnoush; Facciolla, Violeta Lescher; Anantharaman, Devasena; Chopard, Priscilia; Calvez-Kelm, Florence Le; Vilensky, Marta; Polesel, Jerry; Holcatova, Ivana; Simonato, Lorenzo; et al. (Oncotarget, 2017)
The use of non-invasive biomarkers such as circulating tumor DNA (ctDNA) in head and neck tumors may be of relevance in early diagnosis and eventually improved outcome. We evaluated two different approaches from two case series in Europe and South America including (i) targeted screening of ctDNA mutations, and (ii) detection of TP53 mutations in plasma and oral rinses without previous knowledge of mutational status in tumor samples. Targeted sequencing in 5 genes identified ctDNA mutations in plasma among 42% of HNSCC cases, 67% of who were early stage cases. No association was found between ctDNA mutation detection and overall survival. Sequencing of the entire coding region of the TP53 gene resulted in identification of TP53 mutations in 76% of tumor cases. However, concordance of mutation detection was low between tumor, oral rinses (11%) and plasma (2,7%) samples. Identification of 5 pathogenic TP53 mutations in oral rinses from 3 non-cancer controls gives additional evidence of mutation occurrence in individuals without a diagnosed cancer and presents an additional challenge for the development of ctDNA diagnostic assays.
Keywords: cancer; ctDNA; mutation; detection; head and neck